Short-term changes in klotho and FGF23 in heart failure with reduced ejection fraction—a substudy of the DAPA-VO2 study - Mora-Fernández, Carmen; Pérez, Adora; Mollar, Anna; Palau, Patricia; Amiguet, Martina; de la Espriella, Rafael; Sanchis, Juan; Górriz, Jose Luis; Soler, María José; Navarro-González, Juan F.; Núñez, Julio, DAPA-VO2 Investigators; et al. (Frontiers in Cardiovascular Medicine, 2023)
The klotho and fibroblast growth factor 23 (FGF-23) pathway is implicated in cardiovascular pathophysiology. This substudy aimed to assess the changes in klotho and FGF-23 levels 1-month after dapagliflozin in patients with stable heart failure and reduced ejection fraction (HFrEF). The study included 29 patients (32.2% of the total), with 14 assigned to the placebo group and 15 to the dapagliflozin, as part of the double-blind, randomized clinical trial [DAPA-VO2 (NCT04197635)]. Blood samples were collected at baseline and after 30 days, and Klotho and FGF-23 levels were measured using ELISA Kits. Between-treatment changes (raw data) were analyzed by using the Mann-Whitney test and expressed as median (p25%–p75%). Linear regression models were utilized to analyze changes in the logarithm (log) of klotho and FGF-23. The median age was 68.3 years (60.8–72.1), with 79.3% male and 81.5% classified as NYHA II. The baseline medians of left ventricular ejection fraction, glomerular filtration rate, NT-proBNP, klotho, and FGF-23 were 35.8% (30.5–37.8), 67.4 ml/min/1.73 m2 (50.7–82.8), 1,285 pg/ml (898–2,305), 623.4 pg/ml (533.5–736.6), and 72.6 RU/ml (62.6–96.1), respectively. The baseline mean peak oxygen uptake was 13.1 ± 4.0 ml/kg/min. Compared to placebo, patients on dapagliflozin showed a significant median increase of klotho [Δ+29.5, (12.9–37.2); p = 0.009] and a non-significant decrease of FGF-23 [Δ−4.6, (−1.7 to −5.4); p = 0.051]. A significant increase in log-klotho (p = 0.011) and a decrease in log-FGF-23 (p = 0.040) were found in the inferential analysis. In conclusion, in patients with stable HFrEF, dapagliflozin led to a short-term increase in klotho and a decrease in FGF-23.